Classification of physical education of adolescent by subjects of pedagogical influence - T.S. Bondar (Physical Education of Students, 2013)
The classification of adolescent’s physical education by subjects of primary pedagogical influence is considered. The study involved 648 adolescents aged 11-15 years. Found that in today's society there was a system of organizing leisure activities adolescents with primary pedagogical influence of subjects. States that schools should promote the introduction of new forms of physical activity, innovative and interactive technologies. Emphasizes the need for a strong self-organization capabilities, self-organization of active leisure for teenagers. Select the form of motor activity with the independent power of teenagers decisions, motives and interests. Shown the form of decision-making under the influence of adolescent parents and people around them. Recommended the formation of accounting for physical education in the education system include documentation of all forms of physical activity.